Education on citizenship as a social responsibility in the curriculum- analyze content the subject of citizenship in the book of civic education for the third year is medium. - Dilmi, Raouia; Zellagui, Wahiba (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The purpose of this study is to introduce citizenship education as a social responsibility in the curriculum. In order to carry out this study, the content analysis curriculum has been used, drawing on the medium third year of civic education, specifically the citizenship course. The educational system is therefore entrusted with the task of socialization, which is not the easy task of gathering information. It is a carefully structured goal of inculcating values in young people. The school gives the pupil the content, information and concepts that are the first rule, and the basic data on which the pupil clues early. In order to inculcate these values in young people, it was necessary to rely on the educational system, which considers the school to be the most important institution for socialization, which indoctrinates the principles of citizenship, such as freedom of expression, rights and duties, and inculcates its values through its curriculum. This is what we seek in all the books of the various stages of education.